Analysis of Consumption Patterns of Poor Households in Bone Bolango Regency - Suriati; Sri Endang Saleh; Sri Indriyani S. Dai (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This study aims to analyze the Consumption Patterns of Poor Households in Bone Bolango Regency and examine the effect of household expenditures on food and non-food needs on poverty levels. The approach used is quantitative with binary logistic regression analysis. Secondary data sourced from the 2023 National Socioeconomic Survey (SUSENAS) obtained through the Central Statistics Agency (BPS) of Bone Bolango Regency are used. The test results show a positive effect on the consumption patterns of poor households, while the expenditure variable has no significant effect.